Muslim Women's Studies: Two Contributions (American Journal of Islam and Society, 1996)
Politics, Gender, and the Islamic Past: The Legacy of Aisha hint Abi Bakr.By D. A. Spellberg. New York: Columbia University Press, 1994, 243 pp.Qur'an and Woman. By Amina Wadud-Muhsin. Kuala Lumpur: FajarBakti, 1992, 118 pp.Denise Spellberg's survey of the legacy of 'A'ishah and AminaWadud-Muhsin's exegesis of the Qur'anic exposition of gender are foraysin the field of Muslim women's studies. Both works study the place ofMuslim women in the textual heritage of the community, but their pointsof departure are different. Spellberg proposes that 'A'ishah's legacy, aproduct of exclusively male writings in texts from the classical Islamiccenturies, is a reflection of Muslim men's interpretations of early Islamichistory and their opinions about the proper place of women in their owntime. Such interpretations, Spellberg shows, are charged with the politicaltensions of their contemporary societies. Yet 'A'ishah 's "legacy alonedefied idealization as completely as it denied comfortable categorization"by the Muslim men whose texts represent and construct her, Spellbergasserts (p. 190).Wadud-Muhsin acknowledges the way in which another copiousIslamic scholarship emerged, motivated by the need to understand theQur'anic utterances about women. Her focus is not, however, on thoseinterpretive texts of men that form an authoritative tradition explaining themeaning of the Qur'an. Wadud-Muhsin argues that the question ofwoman in the Qur'an must be reconnected directly to the primary text.She proposes approaching the Qur'anic text without the assumptions aboutgender of the classical interpreters, whose work constitutes the Islamic traditionof exegesis, but also without the assumptions that undergird contemporaryfeminist readings of the Qur'an. She offers a herrneneuticalmethod for understanding the place and meaning of gender in the Qur'an,based on the consistencies of the Qur'an itself: its contexts, language, andthe worldview of its texts as a whole. The effect of this, Wadud-Muhsinsuggests, would be to transcend the gender biases of narrower readingmethods and arrive at a fuller appreciation of the text's guidance for menand women.Both works began as dissertations, Spellberg's in history, WadudMuhsin'sin religious studies. Each brings to Muslim women's studies anode of questions about the process of textual interpretation. The ...